Error monitoring Strategy in writing activities of English Department Students - Zulkifli, Nur Aisyah (Journal of English and Arabic Language Teaching, 2013)
The term of writing can not be seperated from English Department Students. It is a part of students’ skill to see whether they are able to use English well or not in their daily life. Moreover, They are not only able to use  in spoken language but also are able to express their ideas in writing form. Writing ability is specific ability which helps students to put their ideas into words in meaningful form and interract with the message.It can not be denied, there are some problem faced by students in writing. It may be related to garammatical form, coherence and cohesion of paragraph, spelling, etc. However, it is still a process. The problem right now is how to make studets aware about their mistake or error in writing. Therefore, in this article writer will disscuss about the strategy that can be used by students. It is Error Monitoring Strategy. Error monitoring strategy is a learning strategy that helps students systematically question themselves regarding capitalization, overall appearance, punctuation, and spelling errors in their written products, as well as correct them, before submitting the assignment to the lecturer.